In vitro evaluation of S-(+)-ibuprofen as drug candidate for intra-articular drug delivery system. (30th October 2013) - Bédouet, Laurent; Pascale, Florentina; Bonneau, Michel; Laurent, Alexandre
Abstract: Intra-articular drug delivery systems (DDSs) are envisaged as interesting alternative to locally release non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen to reduce pain in patients with osteoarthritis. The present study examines the efficacy of S-(+)-ibuprofen on cartilage degradation as drug candidate for DDS loading. Humeral cartilage and joint capsule explants were collected from healthy sheep shoulder joints and they were cultured in mono- or in co-culture for 13 days with LPS in combination with S-(+)-ibuprofen at 50 µM and 1 mM. S-(+)-ibuprofen (50 µM) blocked prostaglandins production in LPS-activated explants but did not reduce cartilage degradation. By contrast, 1 mM S-(+)-ibuprofen treatment of cartilage explants reduced nitric oxide synthesis by 51% ( p  = 0.0072), proteoglycans degradation by 35% ( p  = 0.0114) and expression of serum amyloid protein – the main protein induced upon LPS challenge – by 44% ( p  < 0.0001). On contrary, in presence of synovial membrane, the protective effects of S-(+)-ibuprofen on cartilage damages were significantly diminished. At 1mM, S-(+)-ibuprofen reduced the cell lysis during culture of cartilage and joint capsule either in mono- or in co-culture. This study performed on sheep explants shows that 1 mM S-(+)-ibuprofen inhibited cartilage degradation via a mechanism independent of cyclooxygenase inhibition. Reduction of prostaglandins synthesis at 50 µM in all treatment groups and reduction of cartilage degradation observed at 1 mM suggest that S-(+)-ibuprofen could be considered as a promising drug candidate for the loading of intra-articular DDS.